Strategia regionu legnicko-zgorzeleckiego a jego potrzeby kadrowe - Kral, Zygmunt; Krawczyszyn, Franciszek (Strategy of Legnica and Zgorzelec Region versus Its Personnel Needs, 2007)
Strategic significance of Legnica and Zgorzelec region was pointed out to. Opportunities and threats of this region plus strengths and weaknesses were determined. In this context strategic goals of the region and its tasks were listed. The problem of demand for personnel in this region over the spectrum of the present situation on the local labour market and the strategy of local development were considered. The jobs specially needed from the point of view of the region development were listed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 174-180